2017
DOI: 10.1177/1010428317699755
|View full text |Cite
|
Sign up to set email alerts
|

Association of Wnt1-inducible signaling pathway protein-1 with the proliferation, migration and invasion in gastric cancer cells

Abstract: Wnt1-inducible signaling pathway protein-1 is a cysteine-rich protein that belongs to the CCN family, which has been implicated in mediating the occurrence and progression through distinct molecular mechanisms in several tumor types. However, the association of Wnt1-inducible signaling pathway protein-1 with gastric cancer and the related molecular mechanisms remain to be elucidated. Therefore, this study aimed to clarify the biological role of Wnt1-inducible signaling pathway protein-1 in the proliferation, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Based on the involvement of CCN4 in many other cancers, Jia et al tested whether there was an association of CCN4 with gastric cancer 29. This group determined that CCN4 mRNA levels were elevated in gastric cancer specimens, and that CCN4 was expressed in gastric carcinoma cell lines.…”
Section: Gastric Cancermentioning
confidence: 99%
“…Based on the involvement of CCN4 in many other cancers, Jia et al tested whether there was an association of CCN4 with gastric cancer 29. This group determined that CCN4 mRNA levels were elevated in gastric cancer specimens, and that CCN4 was expressed in gastric carcinoma cell lines.…”
Section: Gastric Cancermentioning
confidence: 99%
“…Notably, the CCN (Cyr61, CTGF, and NOV) membrane proteins are essential in tumorigenesis and metastasis 15 . The CNN family also plays regulatory roles in angiogenesis and tumorigenesis 16 . Our previous work indicates that CCN6 regulates metastasis in chondrosarcoma, enhancing chondrosarcoma cell migration by increasing levels of ICAM-1 expression 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has also demonstrated that Tp53 mutation may promote WISP1 expression in mouse PDAC cells ( Wang et al, 2015 ). Recent studies had shown that WISP1 acts as a new oncogene in glioblastoma ( Jing et al, 2017 ), oral squamous cell carcinoma ( Jung et al, 2017 ), gastric cancer ( Jia et al, 2017 ), melanoma ( Shao et al, 2016 ), and colon cancer ( Wu et al, 2016 ). Also, Yang et al (2015) showed that patients with high expression of WISP-1 had a shorter survival time independent of clinical stage and lymphatic metastasis status in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%